Partnership Selection and Formation: A Case Study of Developing Adolescent Health Community-Researcher Partnerships in 15 U.S. Communities - Straub, Diane M. (2007)
PURPOSE: This study describes the partner selection process in 15 U.S. communities developing community-researcher partnerships for the Connect to Protect® (C2P): Partnerships for Youth Prevention Interventions, an initiative of the Adolescent Trials Network for HIV/AIDS Interventions. METHODS: Each site generated an epidemiological profile of urban youth in their community, selected a focus population and geographic area of youth at risk for HIV, conducted a series of successive structured interviews, and engaged in a process of relationship-building efforts culminating in a collaborative network of community agencies. RESULTS: Sites chose as their primary target population young women who have sex with men (n=8 sites), young men who have sex with men (n=6), and intravenous drug users (n=1). Of 1,162 agencies initially interviewed, 281 of 335 approached (84%) agreed to join the partnership (average 19/site). A diverse array of community agencies were represented in the final collaborative network; specific characteristics included: 93% served the sites' target population, 54% were predominantly youth-oriented, 59% were located in the geographical area of focus, and 39% reported provision of HIV/STI prevention services. Relationship-building activities, development of collaborative relationships, and lessons learned, including barriers and facilitators to partnership, are also described. CONCLUSIONS: Study findings address a major gap in the community partner research literature. Health researchers and policy makers need an effective partner selection framework whereby community-researcher partnerships can develop a solid foundation to address public health concerns.